Nitrogen-groundwater pollution prediction using expert system for an agricultural area - Mongkon, Ta-Oun; Daud, Mohamed; Bardaie, Mohd Zohadie; Jusop, Shamshuddin (Universiti Putra Malaysia, 1999)
This study was initiated to collect data for the knowledge base for investigation of crops types, data of physical and biological framework, nitrogen fertilizer rate and crops area. The objective is to predict the effects of agricultural development on groundwater pollution potential from nitrogen fertilizer which depend on each of environment of Cameron Highland area by using application of expert system. Knowledge base in this study can be divided into two parts; the first part includes collection of relevant information and the second part is the coding of knowledge for the problem domain. The sources of knowledge base can be carried from established literature and domain expert. An expert system was developed using CLIPS(C Language Integrated Production System). This expert system is an important module for new users of the system. Users are able to extract that knowledge from this module. The system provides an example of a qualitative and logic based technique for analysis of complex groundwater environmental impact assessment problems. All information is available in a consistent and plausible framework that links agricultural activities in Cameron Highland. The Nitrogen groundwater pollution prediction is based on physical and hydrological framework by considering together the factors of nitrogen fertilizer application.